Artificial Intelligence in Purchasing: Facilitating Mechanism Design-based Negotiations. Issue 8 (2nd July 2020) - Schulze-Horn, Ines; Hueren, Sabrina; Scheffler, Paul; Schiele, Holger
ABSTRACT: Negotiations are central to reach consensus between supply chain partners while, simultaneously, meeting internal cost and quality targets. Purchasing prices can be improved by inducing competition in the supply base. In this context, the application of mechanism design theory in negotiations gained enhanced attention. While such approaches can result in high cost reductions, mechanism design-based negotiations are very complex. The paper aims at answering the question whether artificial intelligence (AI) can facilitate the execution of mechanism design-based negotiations. To this end, a World Café has been conducted at an automotive original equipment manufacturer. A group of 20 experts from the fields of purchasing and AI discussed the potentials of AI for the purchasing function. The results indicate that the application of AI can indeed facilitate the execution of mechanism design-based negotiations and help overcoming bounded rationality problems. Even more, AI might be a game changer for the purchasing function.